2000
DOI: 10.4315/0362-028x-63.7.871
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Salmonella spp. and Strains of Escherichia coli O157:H7 by Gamma Radiation of Inoculated Sprouts

Abstract: There have been several recent outbreaks of salmonellosis and infections with Escherichia coli O157:H7 linked to the consumption of raw sprouts. Use of ionizing radiation was investigated as a means to reduce or to totally inactivate these pathogens, if present, on the sprouts. The radiation D value, which is the amount of irradiation in kilograys for a 1-log reduction in cell numbers, for these pathogens was established using a minimum of five doses at 19 +/- 1 degrees C. Before inoculation, the sprouts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
4
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 17 publications
2
49
4
3
Order By: Relevance
“…The D 10 values of 43894 ranged from 14 to 27% less than those of the other two strains. Straindependent response to irradiation is a well-documented phenomenon and has been previously observed with E. coli O157:H7 irradiated on a variety of food and nonfood substrates (14,17,21,24). However, this is the first direct examination of the role of isolate specificity with regard to the radiation sensitivity of biofilm-associated E. coli O157:H7 cells.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The D 10 values of 43894 ranged from 14 to 27% less than those of the other two strains. Straindependent response to irradiation is a well-documented phenomenon and has been previously observed with E. coli O157:H7 irradiated on a variety of food and nonfood substrates (14,17,21,24). However, this is the first direct examination of the role of isolate specificity with regard to the radiation sensitivity of biofilm-associated E. coli O157:H7 cells.…”
Section: Resultsmentioning
confidence: 91%
“…The radiation dose value required to reduce the population by one log or 90% (D 10 ) for E. coli O157:H7 depends on the isolate, the suspending food product, and the conditions of treatment (13,14,21). When inoculated onto fresh sprouts of radish, alfalfa, or broccoli seeds, E. coli O157:H7 showed a D 10 value range of 0.27 to 0.34 kGy, depending on the type of sprout examined (17). On different types of lettuce, D 10 values of between 0.12 and 0.14 kGy were reported, depending on the suspending type of lettuce (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…are important food-borne pathogens, responsible for food-borne illness (FBI) associated with a variety of food products (16,18,19,24). Numerous studies have documented the ability of Salmonella spp.…”
mentioning
confidence: 99%
“…Yet studies have shown that this results in a median reduction of only 2.5 log CFU/g (20). Other sanitizing treatments include ionizing radiation (21), high hydrostatic pressure (22) in combination with mild heat (23), supercritical carbon dioxide (24), hot water (25)(26)(27), and dry heat (28). There is, however, no decontamination method available to date to ensure elimination of pathogens in all types of seeds without reducing seed germination or sprout yields (2).…”
mentioning
confidence: 99%